Analisis Tipe Kepribadian dan Minat Karir Mahasiswa Berdasarkan Teori Holland (RIASEC) - Saputra, Noris Dwi; Delianti, Vera Irma; Marta, Rizkayeni; Asmara, Delvi (Lembaga Yasin AlSys, 2025)
Career selection is a strategic process for university students in determining a future path aligned with their potential, interests, and personality traits. Students of the Informatics Engineering Education Program at Universitas Negeri Padang face diverse career opportunities, necessitating accurate mapping of personality types and career interests to support more targeted career decision-making. This study aims to examine the construct validity and reliability of students' personality types and career interests based on Holland’s RIASEC theory, which classifies individuals into six personality types correlated with specific career tendencies. A quantitative approach was employed using Confirmatory Factor Analysis (CFA). The sample consisted of 51 active students from the 2021 cohort, selected using Slovin’s formula from a total population of 104. The research instrument was a closed-ended questionnaire adapted from the Self-Directed Search (SDS), utilizing a 5-point Likert scale and analyzed with SmartPLS 4 software. The analysis showed that all indicators had outer loading values > 0.70 and Average Variance Extracted (AVE) > 0.50. Additionally, Cronbach’s Alpha and Composite Reliability values exceeded 0.90, indicating excellent instrument reliability. The Standardized Root Mean Square Residual (SRMR) values were 0.074 for the personality model and 0.071 for the career interest model, demonstrating acceptable model fit. These findings confirm that the personality and career interest models based on Holland’s theory are valid and reliable, and may serve as a foundation for the development of structured, data-driven assessment instruments and career guidance services.